PANCASILA AS A SOURCE OF LAW - Davina Cheysia Syafira; Habibi Farrelino; Nazhifa Zhafira Zea; Risky Fazar Ramadhani; Sabarina Tahlita Aisyah (LEX SOCIETAS: Journal of Law and Public Administration, 2024)
This study aims to analyze the influence of understanding Pancasila as the foundation of the Indonesian state not only functions as a political philosophy, but also as a source of law that guides national and state life. The 5th principle of Pancasila, "Social Justice for All Indonesian People," emphasizes the importance of justice and welfare in every aspect of life. In the context of law, this principle serves as a guideline for formulating public policies that are oriented towards the welfare of society, as well as fair law enforcement. The implementation of the principle of social justice in the legal system in Indonesia includes the protection of human rights, equal opportunities, and poverty alleviation. Therefore, Pancasila, especially the 5th principle, has a crucial role in creating a legal order that is responsive to the needs of society, as well as encouraging active participation of the people in the national development process